Optical control of GPR40 signalling in pancreatic β-cells - Frank, James Allen; Yushchenko, Dmytro A; Fine, Nicholas H F; Duca, Margherita; Citir, Mevlut; Broichhagen, Johannes; Hodson, David J; Schultz, Carsten; Trauner, Dirk (Chemical science, 2017)
Fatty acids activate GPR40 and K+ channels to modulate β-cell function. Herein, we describe the design and synthesis of FAAzo-10, a light-controllable GPR40 agonist based on Gw-9508. FAAzo-10 is a potent GPR40 agonist in the trans-configuration and can be inactivated on isomerization to cis with UV-A light. Irradiation with blue light reverses this effect, allowing FAAzo-10 activity to be cycled ON and OFF with a high degree of spatiotemporal precision. In dissociated primary mouse β-cells, FAAzo-10 also inactivates voltage-activated and ATP-sensitive K+ channels, and allows us to control glucose-stimulated Ca2+ oscillations in whole islets with light. As such, FAAzo-10 is a useful tool to study the complex effects, with high specificity, which FA-derivatives such as Gw-9508 exert at multiple targets in mouse β-cells.